2012
DOI: 10.1002/aic.13777
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic effects in capillary pressure relationships for two‐phase flow in porous media: Experiments and numerical analyses

Abstract: in Wiley Online Library (wileyonlinelibrary.com).Well defined experiments and numerical analyses are conducted to determine the importance of dynamic effect in capillary pressure relationships for two-phase flow in porous media. Dynamic and quasi-static capillary pressure-saturation (P c -S w ) and, qS w /qt-t curves are determined. These are then used to determine the dynamic effects, indicated by a dynamic coefficient () in the porous domains which establishes the speed at which flow equilibrium (qS w /qt ¼ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
110
1
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 68 publications
(121 citation statements)
references
References 21 publications
9
110
1
1
Order By: Relevance
“…This saturation-rate dependency of the system properties observed during non-steady state two-phase flow is referred to as dynamic capillary pressure effects [15] and a large body of literature involving experimental, modeling and theoretical studies has emerged concerning these phenomena [3,4,7,13,[15][16][17][18][19][20][21][22][23][24][25]. Studies by Stauffer [23], Kalaydjian [18], Hassanizadeh and Gray [26] suggest that an extension of the P c -S w function should include a saturation rate dependent term.…”
Section: Introductionmentioning
confidence: 99%
“…This saturation-rate dependency of the system properties observed during non-steady state two-phase flow is referred to as dynamic capillary pressure effects [15] and a large body of literature involving experimental, modeling and theoretical studies has emerged concerning these phenomena [3,4,7,13,[15][16][17][18][19][20][21][22][23][24][25]. Studies by Stauffer [23], Kalaydjian [18], Hassanizadeh and Gray [26] suggest that an extension of the P c -S w function should include a saturation rate dependent term.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, it has been shown that the heterogeneity in porous media affects the dynamic coefficient significantly by altering the rate to flow equilibrium (Manthey et al 2005;Mirzaei and Das 2007;Sakaki et al 2010;Das and Mirzaei 2013). Das et al (2007) and Das and Mirzaei (2013) show that the dynamic coefficient in heterogeneous domain is higher than in homogeneous domain implying that the two-phase flow system reaches equilibrium earlier in the homogeneous domain at a given water saturation.…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, a number of studies have determined the significance of τ in different circumstances Dahle et al 2005;Manthey et al 2005;Das et al 2007Das et al , 2014Das 2007, 2013;Peszynska and Yi 2008;Juanes 2009;Sakaki et al 2010;Bottero et al 2011;Mumford and O'Carroll 2011;Hanspal and Das 2012;Mirzaei 2012, 2013;Hanspal et al 2013;Hou et al 2014;Zhang et al 2014). In particular, it has been shown that the heterogeneity in porous media affects the dynamic coefficient significantly by altering the rate to flow equilibrium (Manthey et al 2005;Mirzaei and Das 2007;Sakaki et al 2010;Das and Mirzaei 2013).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations